Pengaruh Ukuran Perusahaan, Leverage, Dan Profitabilitas Terhadap Praktik Manajemen Laba - Felicya Nathaly; Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study is to examine the influence of firm size, leverage, danprofitability towards earnings management practice in manufacturing companies listed inIndonesia Stock Exchange from periode 2017 – 2019. This study used 75 data samples frommanufacturing companies that have been selected using purposive sampling method with total225 data samples for 3 years. This study used EViews version 11 program to process data. Theresults obtained in this study, firm size and profitability have positive significant influencetowards earnings management practice, while leverage has insignificant influence towardsearnings management practice.